2018
DOI: 10.1108/nfs-10-2017-0212
|View full text |Cite
|
Sign up to set email alerts
|

Preservative potential of Tinospora cordifolia, a novel natural ingredient for improved lipid oxidative stability and storage quality of chevon sausages

Abstract: Purpose The purpose of this study was to assess the preservative potential of Tinospora cordifolia as a novel natural preservative in muscle foods. Design/methodology/approach Chevon sausages were used as a model system and were prepared by incorporating different levels of T. cordifolia, namely, T1 (0.25 per cent), T2 (0.50 per cent) and T3 (0.75 per cent), and assessed for lipid oxidative stability and storage quality under refrigerated (4 ± 10°C) conditions. Findings Lipid oxidative stability showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
1
15
1
Order By: Relevance
“…The principal constituents in the extract were tinsporine, tinosporide, tinosporaside, tinosporon, tinosporic acid, tinosporol, heptacosanol, cordifol, cordifolide, diterpenoid furanolactone tinosporidine, clerodane furano diterpene, columbin, chasmanthin, palmarin, berberine and β‐sitosterol (The Himalaya Drug Company, ). The antimicrobial and antioxidant properties of T. cordifolia extract used in this study have been demonstrated in our previous work on chevon sausages (Kalem, Bhat, Kumar, & Jayawardena, ).…”
Section: Methodsmentioning
confidence: 52%
See 4 more Smart Citations
“…The principal constituents in the extract were tinsporine, tinosporide, tinosporaside, tinosporon, tinosporic acid, tinosporol, heptacosanol, cordifol, cordifolide, diterpenoid furanolactone tinosporidine, clerodane furano diterpene, columbin, chasmanthin, palmarin, berberine and β‐sitosterol (The Himalaya Drug Company, ). The antimicrobial and antioxidant properties of T. cordifolia extract used in this study have been demonstrated in our previous work on chevon sausages (Kalem, Bhat, Kumar, & Jayawardena, ).…”
Section: Methodsmentioning
confidence: 52%
“…The application of biomolecules with antimicrobial and antioxidant properties for the development of edible films for preservation and shelf life extension of pre-cooked muscle foods is an innovative but poorly explored area and more extensive research is required to increase our understanding (Akcan et al, 2017;Kalem, Bhat, Kumar, Noor, et al, 2018). Polyphenol-rich plant extracts, such as T. cordifolia, are recognized as potent additives for production of bioactive edible films to retard the changes associated with microbial spoilage and lipid oxidation (Kalem, Bhat, Kumar, & Jayawardena, 2018).…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations